Adaptations of carbapenem resistant Acinetobacter baumannii (CRAB) in the hospital environment causing sustained outbreak. Issue 3 (19th March 2021) - Sharma, Swati; Das, Arghya; Banerjee, Tuhina; Barman, Hiranmay; Yadav, Ghanshyam; Kumar, Ashok
Abstract : Introduction. Carbapenem resistance in Acinetobacter baumannii ( A. baumannii ) is an emerging global threat. Gap statement. The adaptation strategies of A. baumannii for this emergence as a nosocomial pathogen has been less studied. Aim. This prospective study analysed a sustained outbreak of carbapenem resistant Acinetobacter baumannii (CRAB) in the intensive care unit (ICU) with reference to antimicrobial resistance and virulence in the colonizing and pathogenic isolates under carbapenem stress. Results. The CRAB isolates from initial and sustained outbreak were found harbouring multiple carbapenemase genes. These genes included bla OXA-23, bla IMP, bla VIM and bla NDM . From NICU environment three phenotypically carbapenem susceptible isolates were found carrying bla OXA-23, bla IMP, bla VIM genes. Prior imipenem therapy was one of the risk factors ( P =0.0016). The outbreak was polyclonal. Under imipenem stress, outbreak isolates showed no loss of carbapenemase genes against stress free conditions (23.7±1.33 days). Biofilm formation increased with imipenem concentration, with outbreak isolates producing highest biomass. While the pathogens showed a slow growth rate on imipenem exposure, the colonisers grew rapidly ( P <0.0001). Methods. Sustained outbreak of CRAB was identified in the ICU (July 2015 to December 2017). Risk factors for acquisition of CRAB was studied. A. baumannii isolates were also collected from the environments of ICU and neonatal ICU (NICU) and blood cultures of septic neonates. Isolates were characterized based on antimicrobial susceptibility, genetic profile, integrons carriage and clonality. Biofilm formation and growth kinetics were studied under varying carbapenem stress. Conclusion. Intense carbapenem exposure in the ICU facilitates persistence of CRAB by several adaptations causing sustained outbreaks.